PRODUCTION AND STORAGE OF Trichothecium roseum TO USE AS BIOPESTICIDE - NEGRI, Genuino; MAY DE MIO, Louise Larissa; WORDELL FILHO, João Américo (Scientia Agraria, 2010)
Trichothecium roseum is a potential antagonistic fungus to control peach Brown rot reducing the pathogen infection and disease damage. The current experiment aimed at developing a methodology for production of the antagonist Trichothecium roseum in different substrates, and to test its viability when stored in several temperatures. The substrates used were brown rice, rice hulls, sorghum grain and wheat grain boiled to tap water for 5, 10 and 20 min and not boiled, with and without added of nutrients with four repetitions. The evaluation of the stored inoculum viability was tested in temperatures: -4, 4, 15, 25, 35 oC and room temperature, for 90 days. The analysis of variance indicated significant interactions among the substrates, the time of boiling and the types of treatment with or without the use of nutrients. The rice and wheat substrates without PD (potato + dextrose) nutrients addition were the more efficients in the production of the antagonist, demonstrating that these do not require the addition of nutrients for multiplication of the fungus. To maintain the viability of the inoculum The best storage condition was at temperature -4 oC, where of rates in viability of the conidia were 74% at 30 days, 44% at 60 days and 32% at 90 days; this temperature can easily be obtained in freezers; therefore, future users do not need to make high investments in equipment for the conservation of the antagonist.